Composite Deck in Two-Dimensional Modelling of Railway Truss Bridge - Wojciech Siekierski (The Baltic Journal of Road and Bridge Engineering)
The paper shows a technique of two-dimensional modelling of railway truss bridge girders. The model accounts for joint action of girders and steel-concrete composite deck. Namely, influence of the deck on span flexural rigidity and internal force distribution in truss members are taken into account. The technique is capable of reflecting various arrangements of cross beam to truss flange connection as well as various concrete slab longitudinal rigidity (uncracked/cracked). Application example of test loaded bridge span is given. The accuracy of assessment of span flexural stiffness and internal forces distribution of presented procedure is similar to 3D beam/shell element model results accuracy. The presented technique is suitable for preliminary design of truss bridges and verification of other computational methods.